Changes of Plant Growth and Soil Physicochemical Properties by Cultivating Different Economic Plant Species in Saline-Alkali Soil of Hetao Oasis, Inner Mongolia - Rong Ma; Fengmei Du; Yongli Qin; Jianping Lv; Guanying Xing; Youjie Xu; Na Fu; Jun Qiao; Guangyu Hong; Shaokun Wang (Agriculture)
Due to prolonged irrigation from the Yellow River, a large area of farmland in the Hetao Oasis has undergone different degrees of salinization and alkalization, leading to reduced crop yields and incapable soil for plant growth. To enhance the productivity of the farmland with saline-alkali soils, it is important to select salt-tolerant economic plant species that are capable of growing under the local climate and soil conditions in the Hetao Oasis. We conducted the experiment by planting Ziziphus jujuba var. spinose, Elaeagnus angustifolia, Hippophae rhamnoides and Lycium chinense in the Bayan Taohai Farm of the Hetao Oasis. Changes of plant growth (the survival rate, plant height, canopy, basal diameter and new branch length) and soil physicochemical properties (soil organic carbon, total carbon, total nitrogen, pH, electrical conductivity and particle size distribution) were continuously monitored during two growing seasons. Results indicated that, by the end of the first growing season, the survival rate of the Z. jujuba was less than 10%, making it unsuitable for plantation in the saline-alkali soils of the Hetao Oasis. In terms of plant growth, the E. angustifolia exhibited the highest survival rate (94.71%) and the fastest growth rate, indicating that E. angustifolia is adapted in the saline-alkali soils of the Hetao Oasis. The survival rates for L. chinense and H. rhamnoides were 86.46% and 65.64%, respectively, indicating that these species could grow in the saline-alkali soils, but at a slower rate. From the perspective of soil improvement, E. angustifolia, H. rhamnoides and L. chinense could reduce the soil pH, and E. angustifolia could significantly increase soil nutrients. In conclusion, it is not recommended to plant Z. jujuba, while the E. angustifolia is recommended as a proper economic species to be widely planted in the saline-alkali soils of the Hetao Oasis. H. rhamnoides could be selectively planted in areas with better soil conditions, and the L. chinense could be planted following soil improvement measurements. The research enhanced the effective utilization of the saline-alkali farmland and provided proper economic plant species for sustainable agriculture management in the Hetao Oasis of Inner Mongolia.